The Impact of Dual Apprenticeship Programs on Early Labour Market Outcomes: A Dynamic Approach - Brecht Neyt; Dieter Verhaest; Stijn Baert (Institute of Labor Economics (IZA), 2018)
This study examines the impact of enrolling into dual apprenticeship programs in secondary education on six early employment outcomes. Our contribution to the literature is threefold. First, we estimate – within the same, Belgian secondary education framework – the effects of two distinct types of dual programs that combine part-time school- or training centre-based instruction with an apprenticeship in a firm. Second, these effects are identified by estimating a dynamic model capturing subsequent educational and labour market outcomes to control for the dynamic selection of students into dual programs. Third, this approach enables us to distinguish between the programs' direct effects (conditional on educational achievement) and indirect effects (via educational achievement). We find evidence for short-term labour market advantages but only for the program with the most days of in-field training. With these findings we contribute to the international discussion on the optimal design of vocational programs.
Keywords: I21; I26; J21; 330; vocational education; transitions in youth; dynamic selection; education; labour